Demonic grounds : black women and the cartographies of struggle - McKittrick, Katherine (Minneapolis : University of Minnesota Press, 2006)
"Demonic Grounds moves between past and present, archives and fiction, theory and everyday, to focus on places negotiated by black women during and after the transatlantic slave trade. Specifically, Katherine McKittrick addresses the geographic implications of slave auction blocks, Harriet Jacobs's attic, black Canada and New France, as well as the conceptual spaces of feminism and Sylvia Wynter's philosophies." --Publisher's description.
Introduction : geographic stories -- I lost an arm on my last trip home : Black geographies -- The last place they thought of : Black women's geographies -- The authenticity of this story has not been documented : auction blocks -- Nothing's shocking : Black Canada -- Demonic grounds : Sylvia Wynter -- Conclusion : stay human.
Includes bibliographical references (pages 171-185) and index.
Description based on online resource, title from digital title page (viewed on April 10, 2024)
English.
JSTOR
Keywords: Women, Black -- America -- Social conditions; African diaspora; Human geography -- America; Geography -- Psychological aspects; Slavery -- America -- History; Enslaved women -- America -- History; Women, Black -- Political activity -- America; Women, Black, in literature; America -- Race relations; America -- Geography -- Psychological aspects; Femmes noires -- Amérique -- Conditions sociales; Africains -- Pays étrangers.; Géographie -- Aspect psychologique; Femmes esclaves -- Amérique -- Histoire; Femmes noires -- Activité politique -- Amérique.; Noires dans la littérature.; Amérique -- Relations raciales; Amérique -- Géographie -- Aspect psychologique; SOCIAL SCIENCE -- Women's Studies; SOCIAL SCIENCE -- Ethnic Studies -- African American Studies; African diaspora; Geography -- Psychological aspects; Human geography; Race relations; Slavery; Women, Black, in literature; Women, Black -- Political activity; Women, Black -- Social conditions; Enslaved women; America; History